2006
DOI: 10.1038/nature05372
|View full text |Cite
|
Sign up to set email alerts
|

A human colon cancer cell capable of initiating tumour growth in immunodeficient mice

Abstract: Colon cancer is one of the best-understood neoplasms from a genetic perspective, yet it remains the second most common cause of cancer-related death, indicating that some of its cancer cells are not eradicated by current therapies. What has yet to be established is whether every colon cancer cell possesses the potential to initiate and sustain tumour growth, or whether the tumour is hierarchically organized so that only a subset of cells--cancer stem cells--possess such potential. Here we use renal capsule tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

66
2,913
16
37

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 3,718 publications
(3,032 citation statements)
references
References 25 publications
66
2,913
16
37
Order By: Relevance
“…The first to identify such cells was Al-Hajj who found that breast cancer cells with CD24-CD44+ phenotype are able to form tumors that recapitulate their parental tumor when implanted in the mammary fat pad [26]. Immediately following this discovery, CD133+ cells were identified as tumor stem cells in glioblastoma brain tumors [27] and thereafter in colon cancer [28]. In the past few years, high ALDH1 activity levels have been used to identify CSCs in a variety of tumors including liver, head and neck, colorectal, breast, multiple myeloma, acute myeloid leukemia, and brain cancers [29][30][31][32][33][34][35].…”
Section: Cancer Stem Cells-past and Currentmentioning
confidence: 99%
See 1 more Smart Citation
“…The first to identify such cells was Al-Hajj who found that breast cancer cells with CD24-CD44+ phenotype are able to form tumors that recapitulate their parental tumor when implanted in the mammary fat pad [26]. Immediately following this discovery, CD133+ cells were identified as tumor stem cells in glioblastoma brain tumors [27] and thereafter in colon cancer [28]. In the past few years, high ALDH1 activity levels have been used to identify CSCs in a variety of tumors including liver, head and neck, colorectal, breast, multiple myeloma, acute myeloid leukemia, and brain cancers [29][30][31][32][33][34][35].…”
Section: Cancer Stem Cells-past and Currentmentioning
confidence: 99%
“…Moreover, a link between poor prognosis and increased ALDH1 activity was found in breast tumors [33]. Since the above discoveries, as well as additional CSCs markers, CSCs have been prospectively isolated from a variety of malignancies, thus far including pancreas, skin, head and neck, and prostate cancers, and the list is ever growing [26][27][28][36][37][38]. The identification of CSCs was facilitated by significant progress achieved over the last several years in this field.…”
Section: Cancer Stem Cells-past and Currentmentioning
confidence: 99%
“…To date, the existence of CSCs has been proven in the context of many cancers, including those of leukemia, breast cancer, glioblastoma, prostate cancer, pancreatic cancer and colon cancer (Lapidot et al, 1994;Bonnet and Dick, 1997;Al-Hajj et al, 2003;Hemmati et al, 2003;Singh et al, 2003Singh et al, , 2004Collins et al, 2005;Ponti et al, 2005;Haraguchi et al, 2006;Patrawala et al, 2006;Li et al, 2007;O'Brien et al, 2007;Ricci-Vitiani et al, 2007). Recently, we have determined that HCC is hierarchically organized and originates from a primitive stem/progenitor group of cells for which CD133 þ precursors constitute one of the most immature stage (Ma et al, 2007).…”
mentioning
confidence: 99%
“…To date, CD133 has also been shown to mark the CSC population in cancers of the brain, prostate, pancreas and colon (Hemmati et al, 2003;Singh et al, 2003;Li et al, 2007;O'Brien et al, 2007;Ricci-Vitiani et al, 2007). Preliminary studies have attributed the high expression levels of specific ABC drug transporters to the increased resistance of CD133 CSCs to chemotherapeutic agents (Dean et al, 2005;Haraguchi et al, 2006).…”
mentioning
confidence: 99%
“…Until now, CSCs have been reported in several types of solid tumors, including colorectal, breast, pancreatic, lung, and hepatocellular 49, 50, 51, 52. More and more in vivo evidence demonstrated that CSCs could promote MDR.…”
Section: Mechanisms Of Cancer Multidrug Resistancementioning
confidence: 99%